2013
DOI: 10.1107/s0108270113028965
|View full text |Cite
|
Sign up to set email alerts
|

Tosylate salts of the anticancer drug lapatinib

Abstract: Two tosylate salts of an anticancer drug lapatinib, viz. a monotosylate [systematic name: ({5-[4-({3-chloro-4-[(3-fluorophenyl)methoxy]phenyl}amino)quinazolin-6-yl]furan-2-yl}methyl)[2-(methylsulfonyl)ethyl]azanium 4-methylbenzenesulfonate], C29H27ClFN4O4S(+)·C7H7O3S(-), (I), and a ditosylate [systematic name: 4-({3-chloro-4-[(3-fluorophenyl)methoxy]phenyl}amino)-6-]5-({[2-(methylsulfonyl)ethyl]azaniumyl}methyl)furan-2-yl[quinazolin-1-ium bis(4-methylbenzenesulfonate)], C29H28ClFN4O4S(2+)·2C7H7O3S(-), (II), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In literature, the pKa 1 and pKa 2 values of LPT were given as 3.80 and 7.20, respectively. 23 Figure S1b confirmed that the anionic form of LPT, at pH > 3.80, is more difficult to oxidize than the uncharged form. The 0.1 M H 2 SO 4 was chosen as the supporting electrolyte for further studies.…”
Section: Resultsmentioning
confidence: 64%
“…In literature, the pKa 1 and pKa 2 values of LPT were given as 3.80 and 7.20, respectively. 23 Figure S1b confirmed that the anionic form of LPT, at pH > 3.80, is more difficult to oxidize than the uncharged form. The 0.1 M H 2 SO 4 was chosen as the supporting electrolyte for further studies.…”
Section: Resultsmentioning
confidence: 64%
“…Simulation of protonation constants using iLabs software [4] predicted two calculated pKa macroconstants (5.6 ± 0.4 and 4.7 ± 0.4) emerging from a combination of various protonation microstates, including all three protonable nitrogen atoms. In the known crystal structures of lapatinib tosylate and ditosylate [5] protonation occurred on nitrogen atoms N1 and N1N2 respectively. However, the route of protonation and exact protonation sites in solution, which are important for better understanding of biological activity as well as environmental protection and development of manufacturing technology, still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The search for novel solid-state forms of marketed drugs by crystal engineers and crystallographers has become widespread in recent years (Childs et al, 2004;Blagden et al, 2007;Sridhar & Ravikumar, 2009;Ravikumar et al, 2013;Nechipadappu et al, 2017;Durá n-Palma et al, 2017). Indeed, many advances have been made from studies dealing with polymorphism, solvatomorphism and the cocrystallization of commercial drugs (Babu & Nangia, 2011;Padrela et al, 2017).…”
Section: Introductionmentioning
confidence: 99%